Congenital Heart Disease in Patients With Cleft Lip/Palate and Its Impact on Cleft Management. (August 2020) - Azadgoli, Beina; Munabi, Naikhoba C. O.; Fahradyan, Artur; Auslander, Allyn; McCullough, Meghan; Aflatooni, Nikki; Davidson Ward, Sally L.; Kumar, S. Ram; Sanchez-Lara, Pedro A.; Swanson, Jordan; Magee, William P.
Objective: To evaluate characteristics of congenital heart disease (CHD) in patients with cleft lip and/or palate (CL/P) and assess potential associations with cleft outcomes. Design: Retrospective review of all patients with CL/P who underwent primary cleft treatment from 2009 to 2015. Setting: Children's Hospital Los Angeles, a tertiary hospital. Patients: Exclusion criteria included microform cleft lip diagnosis, international patients, and patients presenting for secondary repair or revision after primary repair at another institution. Main Outcomes Measured: Patient demographics, prenatal and birth characteristics, CL/P characteristics, syndromic status, postoperative complications, and other outcomes were analyzed relative to CHD diagnoses and management. Patients with CL/P with (+CHD) were compared to those without (−CHD) CHD using χ 2 tests and analysis of variance. Results: Among 575 patients with CL/P, 83 (14.4%) had CHD. Congenital heart disease rates were significantly higher in patients with cleft palate (CP) compared to other cleft types (χ 2, P = .009). Eighty-one (97.6%) out of 83 +CHD patients were diagnosed prior to initial CL/P surgical assessment. Twenty-three (27.7%) +CHD patients required surgical repair of 10 cardiac anomalies prior to cleft care. Congenital heart disease was associated with delayed CP repair and increased rates of fistula in isolated patients with CP. Conclusions: Congenital heart disease is known to be more prevalent in patients with CL/P. These data suggest the condition is particularly increased in patients with CP. Severe forms of CHD are diagnosed and treated prior to cleft care however postoperative fistula may be more common in patients with CHD. Therefore, careful attention is required for patient optimization and palatal flap dissection in patients with coexisting CHD and CL/P.